Monitoring the impacts on the ecosystem integrity of Portelo stream (Douro basin, NE Portugal) after a large spill of mining wastes - Teixeira, Amílcar (2018)
After a period of intense precipitation, in December 2009, a big amount of wastes from an abandoned mine were spilled into Portelo stream, a tributary of Rio Sabor (Douro basin)located in the Montesinho Natural Park (NE Portugal). The wastes covered the riverbed near the mine and some riparian and agricultural downstream areas. From 2010 to 2014 we monitored the impacts of waste spill on the ecosystem integrity, namely in the water chemistry, channel and riparian habitats and on the composition of macroinvertebrate communities. Eight sampling points were selected along the hydric system. Toxicity experiments were developed in laboratory for one fish species, the Northern Iberian barbel (Luciobarbus bocagei), an endemic cyprinid present in the River Sabor. The results showed a big increase of conductivity (>300 μS.cm-1), total suspended solids (> 100 mg.L-1) and a drastic decrease of pH (<5) in the water analyses. It was also detected higher concentrations of copper, aluminium and cobalt in the water (52 physical and chemical parameters were determined, including different heavy metals). Aquatic and riparian habitats were severely disturbed and several metrics (e.g. taxonomic richness, diversity, evenness) confirmed biotic substantial changes in composition and abundance of macroinvertebrate communities. Furthermore, biochemical indicators (Na+and K+ plasmatic concentrations) used in laboratory tests showed to be sensitive, under acute copper exposure of barbel populations (different copper concentrations, 0.06- 0.48 ppm were used), and contributed to justify the disappearance and or reduction of fish species in the affected located in the Montesinho Natural Park. Rehabilitation of disturbed areas must be implemented in order to recover the ecological integrity of the aquatic and riparian ecosystems.